2020
DOI: 10.3389/fpsyt.2020.00677
|View full text |Cite
|
Sign up to set email alerts
|

Amygdalar and Hippocampal Morphometry Abnormalities in First-Episode Schizophrenia Using Deformation-Based Shape Analysis

Abstract: In this study, we investigated and quantified the amygdalar and hippocampal morphometry abnormalities exerted by first-episode schizophrenia using a total of 92 patients and 106 healthy control participants. Magnetic resonance imaging (MRI) based automated segmentation was conducted to obtain the amygdalar and hippocampal segmentations. Disease-versus-control volume differences of the bilateral amygdalas and hippocampi were quantified. In addition, deformation-based statistical shape analysis was employed to q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 59 publications
1
1
0
Order By: Relevance
“…In addition, cortical atrophy is common in SC, which has been reflected in a large number of previous studies [ 25 27 ]. Our research further supports the occurrence of amygdala atrophy in SC, which was supported by the previous results [ 4 , 29 , 30 ]. Previous meta-analysis results showed that the amygdala was asymmetric in MRI volume measurement of normal adults [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…In addition, cortical atrophy is common in SC, which has been reflected in a large number of previous studies [ 25 27 ]. Our research further supports the occurrence of amygdala atrophy in SC, which was supported by the previous results [ 4 , 29 , 30 ]. Previous meta-analysis results showed that the amygdala was asymmetric in MRI volume measurement of normal adults [ 31 ].…”
Section: Discussionsupporting
confidence: 92%
“…It matches local images based on the similarity of contrast and intensity using a robust nonlinear image registration algorithm and is thus capable of detecting boundaries and deformations (21)(22)(23). DBM analyses have been applied to many neurological diseases, including Alzheimer's disease, epilepsy, and schizophrenia, to reveal morphological changes in the brain (21,24,25). However, a thorough search of DBM analysis on HIV+ people yielded only a few studies (15,26,27).…”
Section: Introductionmentioning
confidence: 99%